Emergency congestion management of power systems by static synchronous series compensator - Zaidan, Majeed Rashid; Toos, Saber Izadpanah (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
From a transmission system point of view, any overload on the grid lines during operation in situations such as peak load or emergency conditions include line outage or generator outage, is refers to congestion. Generally, the congestion can be managed by controlling power flow. On the other hand, series compensation has a significant role in control power flow; therefore, series compensation equipment like fixed series capacitor (FSC), thyristor-controlled series capacitor (TCSC), and static synchronous series compensator (SSSC) can be used for congestion management. In this paper, an SSSC is used in a transmission line to manage congestion in emergency conditions, line outage and generator outage. The congestion rent contribution method has been used to determine the location of the SSSC in the IEEE 14-bus test system. This technique finds the transmission line 1-2 (from bus 1 to bus 2) is the best location of the SSSC to reduce congestion. After installing an SSSC in the specified line, simulation results show that the power flow has been controlled, leading to reducing the congestion. In other words, the effectiveness of the SSSC can be seen in reducing the total congestion rent, the total generation cost, and network losses.